Transformative grassroot innovations for sustainable hill agriculture - Singh, Uttam; Singha, A. K.; Mohanty, A. K.; T., Amrutha; Kadhri, Tabasum (Indian Farming, 2025)
The Farmer FIRST Programme, implemented in the ICAR Research Complex for NEH Region, Umiam, Meghalaya, has significantly advanced sustainable and inclusive agricultural development in the north eastern hill region of India. Through participatory and location-specific interventions, the programme has promoted both grassroot innovations and transformative technologies thatutilize locally available resources to enhance productivity, resilience, and rural livelihoods. Notable grassroots innovations include the use of banana pseudo-stems to protect transplanted seedlings from intense sunlight and rainfall, and the utilization of bamboo for constructing low-cost poultry baskets, feeders, irrigation conduits, and aeration systems for fishponds, demonstrating effectiveintegration of Indigenous Technical Knowledge (ITK) with scientific practices. Complementing these, transformative interventions such as second cropping in rice fallows, rabi maize cultivation, orchard establishment, backyard poultry and pig farming, oyster mushroom cultivation, scientific beekeeping, rainwater harvesting, integrated farming systems (IFS), composite fish culture, and farm mechanization through custom hiring centres have enhanced farm productivity, income generation, and resource-use efficiency. Collectively, these efforts have transformed traditional hill farming into a diversified, market-oriented, and environmentally sustainable system, underscoring the vital role of the Farmer FIRST Programme in fostering innovation-driven, climate-resilient, and economicallyviable rural prosperity in Meghalaya and the broader north eastern region.